Property Law and Collective Self-Government - Lavoie, Malcolm (McGill Law Journal / Revue de droit de McGill, 2018)
The property interests of Indigenous communities exhibit distinctive patterns that recur across different countries and in relation to widely differing Indigenous cultures, including in the United States, Canada, Australia, and New Zealand. The principal recurring patterns include alienation restraints, group governance powers as an incident of land tenure, distinctive rules of co-ownership favouring collective governance, and unique collective and individual estates in land. This paper argues that these distinctive doctrinal features can be explained in large part by the functional challenges associated with using property interests in land as a basis for collective self-government. One of the central challenges relates to differences in the optimal scale of various uses that may be pursued on a land base. While uses like housing or farming might best be pursued using individual land titles over relatively small parcels, the collective interest of a group in self-government could require an extensive, contiguous land base occupied by a critical mass of members. The use of land as a locus for a distinctive, self-governing culture is thus an activity that is optimally pursued on a larger scale than would be optimal for most other uses which may be pursued simultaneously. The tension this creates, emerging out of the attempt to manage what the author calls a “cultural semicommons,” is mediated by a distinctive set of institutions. Understanding this functional basis for Indigenous land tenure in common law countries is an important starting point in considering proposals for reform.